Performance and carbon efficiency analysis of biomass via stratified gasifier - Muhammad Iqbal Ahmad; Zainal Alimuddin Zainal Alauddin; Shahril Nizam Mohamed Soid; Mazlan Mohamed; Zairi Ismael Rizman; Mohd Sukhairi Mat Rasat; Mohammad Khairul Azhar Abdul Razab; Mohd Hazim Mohd Amini (2015)
Recent concerns on environment, fuel price and scarcity of its supply have promoted interest in the development of renewable sources as a replacement. This paper aims to show the gasifier experimental finding based on performance and process efficiency. Wood chip was fed in stratified downdraft gasifier with air as gasifying agent. The biomass feeding rate varied from 3 to 4.5 kg/hr with an output of various high heating values (HHV) of producer gas. The study provides a clearer picture of the result obtained from the equivalence ratio (ER) which improvises the gas composition, HHV and carbon conversion efficiency